Screening for distress in BRCA1/2 carriers: a prospective study - Maria Jesus Moura; Fátima Vaz; Juliete Dupont; Paula Rodrigues; Irina Coelho; Ana Luis; Ana Clara; Sandra Bento; Susana Esteves; Joana Parreira (Universidade Católica Portuguesa, Instituto de Ciências da Saúde, 2019)
Introdution: The period of time elapsed after receiving a positive test result, has been previously associated with distress in BRCA1/2 carriers. However, there is a need for reliable instruments and prospective data on distress and perception of risk by those carriers, given the significant increase in demand for BRCA1/2 testing.    Aim: To validate and implement in clinical practice, an instrument for the detection of distress and analysis of risk perception, in individuals that test positive for a BRCA1/2 test.  Materials and Methods: We conducted a prospective study to design and test an instrument (Distress and Risk Perception Questionnaire-DRP) to evaluate distress and risk perception by BRCA1/2 carriers.  Predictive factors for clinically relevant distress, were also explored. Results: One hundred and seventy consecutive, newly diagnosed BRCA1/2 carriers were included (pre-test phase: 21 and test: 149). Distress was measured with the distress thermometer (DT) and DRP, both applied, by telephone, one month after test disclosure. Clinically relevant distress was observed in 40% of the cases. Being a female (OR male vs female=0.37; 95%CI=0.10-1.09) and index patient (OR index vs relative=3.93; 95%CI=1.13-18.37) were independent predictors for distress after adjusting for personal history of cancer. The risk perception was high and no significant correlation with distress was observed with either DT or DRP (Spearman correlation coefficient<0.1 and p>0.05 in both).  Conclusion: DRP is a new scale, easy to administer by telephone, which measures distress and risk perception in BRCA1/2 carriers. Gender and type of genetic screening (being an index patient or a relative) may play a role in the short-term emotional impact of a positive BRCA test result.